2013
DOI: 10.1093/infdis/jit464
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk Oligosaccharides Protect Bladder Epithelial Cells Against Uropathogenic Escherichia coli Invasion and Cytotoxicity

Abstract: The invasive pathogen uropathogenic Escherichia coli (UPEC) is the primary cause of urinary tract infections (UTIs). Recurrent infection that can progress to life-threatening renal failure has remained as a serious global health concern in infants. UPEC adheres to and invades bladder epithelial cells to establish infection. Studies have detected the presence of human milk oligosaccharides (HMOs) in urine of breast-fed, but not formula-fed, neonates. We investigated the mechanisms HMOs deploy to elicit protecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 54 publications
2
57
0
2
Order By: Relevance
“…As a result epithelial cells cannot respond to E.coli bacteria. These effects were only observed with the HMO 3 0 -sialyllactose (3 0 SL) (Lin et al 2014). 2 0 FL HMOs can directly influence inflammatory reactions as well (He et al 2014).…”
Section: Effects Of Hmos On Prevention Of Infection and Support Of Immentioning
confidence: 98%
See 1 more Smart Citation
“…As a result epithelial cells cannot respond to E.coli bacteria. These effects were only observed with the HMO 3 0 -sialyllactose (3 0 SL) (Lin et al 2014). 2 0 FL HMOs can directly influence inflammatory reactions as well (He et al 2014).…”
Section: Effects Of Hmos On Prevention Of Infection and Support Of Immentioning
confidence: 98%
“…Presence of HMOs in urine of infants indicates that HMOs are absorbed into the bloodstream (Rudloff et al 2012). Blood absorbed HMOs have been shown to reduce invasion of uropathogenic Escherichia coli (E. coli) by interacting with ureter epithelial cells, making them more resistant against E. coli invasion by a suppression of intracellular signaling of apoptotic pathways (Lin et al 2014). As a result epithelial cells cannot respond to E.coli bacteria.…”
Section: Effects Of Hmos On Prevention Of Infection and Support Of Immentioning
confidence: 99%
“…For example, Lin et al (2014) showed that pooled HMOs protect bladder epithelial cells against uropathogenic Escherichia coli (UPEC) invasion and cytotoxicity. Although the presence of HMOs did not significantly alter the adhesion to the host cells, a significant reduction was observed in bacterial internalization.…”
Section: Structure-function Associations Of Milk Glycansmentioning
confidence: 99%
“…For example, ␣1-2 fucosylated HMGs, which arise mainly from individuals that are Secretor(ϩ), were observed to prevent the adherence of Campylobacter jejuni to epithelial cells (20) and were associated with protection against diarrhea caused by Campylobacter, caliciviruses, and Escherichia coli toxin in breastfed infants (21)(22)(23). Sialylated HMGs were exclusive receptors for influenza viruses (24 -26) and showed a capacity to inhibit cholera toxin B (27), Vibrio cholera (28), enterotoxigenic E. coli, and uropathogenic E. coli strains (29,30). It was also proposed that HMGs might serve as anti-inflammatory components and thus contribute to the lower incidence of necrotizing enterocolitis in breastfed infants.…”
mentioning
confidence: 99%